Integrating Decision Support Systems in Sustainable Coffee Entrepreneurship: A Feasibility Analysis of Bedhag Kopi’s Robusta Coffee Business in Rural Indonesia - Zein Aufar Putra Suryadipa, Thirafi; Putu Yudhia, Bagus; Alghali Alhafiz Mohamed alnour Albakri, Mohammed (Journal of Supply Chain and Entrepreneurship, 2025)
Background: Sustainable coffee entrepreneurship in rural Indonesia faces persistent challenges in operational efficiency, marketing, and financial management. Bedhag Kopi, a micro-enterprise producing Robusta ground coffee in Jember Regency, exemplifies these constraints within the local agroindustry context. Despite having complete business legality, its managerial structure, production capacity, and marketing strategies remain suboptimal. The growing emphasis on digital transformation and data-driven decision-making offers potential solutions to strengthen business feasibility and sustainability for small coffee producers. Aims: This study aims to evaluate the business feasibility and development potential of Bedhag Kopi by integrating a Decision Support System (DSS) framework. The research focuses on assessing multi-aspect feasibility—including legal, production, marketing, human resources, environmental, and financial dimensions—to identify strategic directions for sustainable business growth. Methods: A descriptive quantitative approach was employed using DSS version 2.0 to analyze the enterprise’s feasibility indicators. Data were collected through structured interviews and financial records, and processed using expert-based scoring analysis to generate performance classifications and development recommendations across business aspects. Results: Findings show that Bedhag Kopi is financially feasible, with a Benefit-Cost Ratio of 1.80, Payback Period of 6.01 years, Net Present Value of IDR 1.48 billion, and Internal Rate of Return of 52.84%. Non-financial aspects—including production, marketing, and human resources—demonstrate moderate feasibility requiring targeted improvement interventions. Conclusion: Integrating DSS into rural coffee entrepreneurship enables systematic evaluation and informed strategic planning. The approach enhances managerial decision-making, financial viability, and environmental sustainability, offering a replicable digital model for small-scale agribusinesses in emerging economies pursuing sustainable competitiveness.